2022
DOI: 10.5888/pcd19.210462
|View full text |Cite
|
Sign up to set email alerts
|

The Occupational Health and Safety of Sign Language Interpreters Working Remotely During the COVID-19 Pandemic

Abstract: Introduction The COVID-19 pandemic has caused a dramatic shift in work conditions, bringing increased attention to the occupational health of remote workers. We aimed to investigate the physical and mental health of sign language interpreters working remotely from home because of the pandemic. Methods We measured the physical and mental health of certified interpreters who worked remotely 10 or more hours per week. We evaluated associations within the overall sample and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Focus groups with interpreters. In previous research, a collective survey was conducted from March through September 2021 to measure interpreters' physical and mental health, 10 perceptions of the remote interpreting implementation process, 15 and experience with the technical aspects and personal impressions of working remotely during the COVID-19 pandemic. Educational institutions, interpreter referral services, nonprofit associations, and video relay service providers shared recruitment material via email listservs, social media, or websites.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Focus groups with interpreters. In previous research, a collective survey was conducted from March through September 2021 to measure interpreters' physical and mental health, 10 perceptions of the remote interpreting implementation process, 15 and experience with the technical aspects and personal impressions of working remotely during the COVID-19 pandemic. Educational institutions, interpreter referral services, nonprofit associations, and video relay service providers shared recruitment material via email listservs, social media, or websites.…”
Section: Participantsmentioning
confidence: 99%
“…Educational institutions, interpreter referral services, nonprofit associations, and video relay service providers shared recruitment material via email listservs, social media, or websites. Respondents identified their primary interpreting setting (staff, educational, community/freelance, video remote, or video relay) and, at the end of the survey, 10,15 the survey asked if they would consider participation in a focus group. We used purposive maximum variation (demographic and geographic) sampling 16 to invite survey respondents to participate in focus groups from June through August 2021.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adults (aged at least 18 years) working remotely as certified sign language interpreters for at least 10 h per week fulfilled the eligibility criteria for completing the DIBQ-SLI. The DIBQ-SLI was administered as part of a larger collective survey instrument used in an overarching study that included measures of the physical and mental health of sign language interpreters across interpreting settings now working remotely from home because of the pandemic (24). Therefore, a power analysis was based on the subjective perception of stress group differences from Rosiner and Shlesinger (25), which indicated that 100 participants would be sufficient to detect a small to medium effect (0.32).…”
Section: Participantsmentioning
confidence: 99%